2002
DOI: 10.1002/j.2161-1912.2002.tb00490.x
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Properties of the Orthogonal Cultural Identification Scale in Asian Americans

Abstract: Reliability (internal consistency and test‐retest) and validity (construct and factorial) of the Orthogonal Cultural Identification Scale (OCIS; E. R. Oetting & F. Beauvais, 1990–1991) were evaluated in a sample of Asian American university students. Ethnic identification, measured using the OCIS, and acculturation, measured using the Suinn‐Lew Asian Self‐Identity Acculturation Scale (R. M. Suinn, K. Rickard‐Fugueroa, S. Lew, & P. Vigil, 1987), are hypothesized to measure related but separate constructs. Análi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…These 2 latent dietary factors are uncorrelated, which implies that a person with a high Japanese food factor score is no more likely to have a low Western food factor score than is a person with a low Japanese food factor score. This observation is consistent with the current understanding that acculturation, when measured in terms of ethnic or cultural identification, is a multidimensional construct in which persons can identify highly with multiple cultures, rather than a one-dimensional continuum in which a person's level of identification with one culture is inversely correlated with his or her identification with another culture (23). This similarity between cultural identification measures and the dietary factors detected here supports the hypothesis that dietary acculturation reflects, or is strongly associated with, more traditional measures of ethnic or cultural identification.…”
Section: Discussionsupporting
confidence: 76%
“…These 2 latent dietary factors are uncorrelated, which implies that a person with a high Japanese food factor score is no more likely to have a low Western food factor score than is a person with a low Japanese food factor score. This observation is consistent with the current understanding that acculturation, when measured in terms of ethnic or cultural identification, is a multidimensional construct in which persons can identify highly with multiple cultures, rather than a one-dimensional continuum in which a person's level of identification with one culture is inversely correlated with his or her identification with another culture (23). This similarity between cultural identification measures and the dietary factors detected here supports the hypothesis that dietary acculturation reflects, or is strongly associated with, more traditional measures of ethnic or cultural identification.…”
Section: Discussionsupporting
confidence: 76%
“…Participants were Asian American undergraduates at a competitive university; caution should therefore be taken in extrapolating present findings to other populations of Asian youth. The distribution of acculturation scores in this sample was comparable to other samples of Asian American students (Johnson et al, 2002); however acculturation variables could relate differently to alcohol use in a broader sample. Reliance on participant reports for assessment of parental drinking limits the accuracy of these data.…”
Section: Discussionsupporting
confidence: 63%
“…In a meta-analysis of nine studies, in which the internal consistency of the SL-ASIA using the coefficient alpha procedure was reviewed, Ponterotto et al (1998) found reliability of .80. A study by Johnson et al (2002) also showed internal consistency with Cronbach's alpha at .80.…”
Section: Suinn-lew Asian Self-identity Acculturation Scalementioning
confidence: 84%